DEVELOPMENT OF AGRICULTURE IS A CRUCIAL FACTOR OF ECONOMIC AND SOCIAL-POLITICAL STABILITY OF OUR COUNTRY - B.K. Nurmaganbetova; A.B.Baimbetova; Zh.A. Dulatbekova; D.D. Karatayev (Academic Journal of Physical and Chemical Sciences, 2019)
The article outlines the importance of development of agriculture as a key factor of economic and social-political stability of the country, its necessity and the ways of development. Our country is committed to entering into the 30 most competitive countries and joining the World Trade Organization and joining the Eurasian Unionwhich imposes a great deal on agriculture sector of our country. Agriculture does not only provide production raw materials in the country, but also plays a major role in solving social problems along with sustainable economic development of the country. Therefore, it is necessary to upgrade the material and technical base with the advanced technologies for agriculture.The current structure of the agricultural production system is based on many forms and forms of production activities. Repair and maintenance of farm equipment and livestock farming equipment, logistics, transport services, agrochemical and veterinary services in the village, work with various moving mechanized groups in agricultural work, production services for agroformations. At present, there are quantitative and qualitative changes in these structures, particularly, repair is being built on a large number of machinetechnological stations on commercial basis on the basis of moving mechanical units of technical enterprises and industrial production units of agro-industrial complex. The diversity of these production services contributes to the economic and social-political stability of the country, in particular, the problem of unemployment.